A importância do yoga na formação da criança - Oliveira, Rafaela Monique Paliares [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present research sought to identify and analyze the benefits of Yoga for the formation of the child in the context of 34 teachers of early childhood education, operating in the Municipal System of teaching of Bauru-SP, which participate in the project Corporeity and Yoga in schools . The study was conducted in accordance with the qualitative approach, characterized as descriptive, using as an open questionnaire data collection. The purpose of investigating the Yoga for children was to broaden the knowledge about this body practice in early childhood education. Whereas Yoga is still little studied and applied to children in schools, the research contributed to spreading the benefits that this activity provides for the formation of the children and encourage teachers to insert this manifestation in the body schools. In summary in the category: Yoga contributions for the child, the teachers considered that Yoga contributes to the knowledge of the body itself, to the tranquility and calm and, likewise, a better concentration through conscious breath, besides contributing to the construction of values and an improvement in motor coordination. In category: Benefits identified with the experience of yoga in school, the teachers observed during the experiences, that Yoga benefits in concentration and in the quiet of the students, another benefit identified by teachers is the knowledge of the body, besides motor development and an increase in cultural repertoire. Concluded with this research, that Yoga is a practice important to the formation of the child in all your with the experiences children have created a domain and a better knowledge of your body, generating a self-confidence and managed to calm down and have a better concentration in class and acquired a larger motor repertoire... (Complete abstract electronic below)

A presente pesquisa buscou identificar e analisar os benefícios do Yoga para a formação da criança na perspectiva de 34 professoras da Educação Infantil, atuantes no Sistema Municipal de Ensino de Bauru-SP, que participaram do projeto Corporeidade e Yoga nas escolas. O estudo foi realizado de acordo com a abordagem qualitativa, caracterizado como descritivo, utilizando como coleta de dados um questionário aberto. A finalidade de investigar o Yoga para crianças consistiu em ampliar o conhecimento a respeito dessa prática corporal na Educação Infantil. Considerando que o Yoga ainda é pouco estudado e aplicado às crianças nas escolas, a pesquisa contribuiu para disseminar os benefícios que essa atividade proporciona para a formação das crianças e incentivar professores a inserir esta manifestação corporal nas escolas. Os resultados apresentaram: Na categoria Contribuições do Yoga para a criança, as professoras consideraram que o Yoga contribui para o conhecimento do próprio corpo, para a tranquilidade e a calma e, do mesmo modo, propicia uma melhor concentração por meio da respiração consciente, além de contribuir para a construção de valores e melhoras na coordenação motora. Já na categoria Benefícios identificados com a vivência de Yoga na escola, as professoras observaram durante as vivências que o Yoga beneficia na concentração e na calma dos alunos. Outro benefício identificado pelas docentes é o conhecimento do corpo, além do desenvolvimento motor e aumento no repertório cultural. Conclui-se que o Yoga é uma prática que contribui para a formação da criança em seu todo, pois com as vivências as crianças criaram um domínio e um conhecimento melhor do seu corpo, gerando autoconfiança e, com isso, conseguiram se acalmar e desenvolver melhor concentração nas aulas, além de adquirirem um novo repertório da cultura corporal... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ioga; Educação de crianças; Educação fisica; Crianças; Yoga